Angiographic Evaluation and Endovascular Treatment Considerations of Brain Arteriovenous Malformations With a Transdural Blood Supply: A Single-Center Experience - Hou, Kun; Xu, Kan; Qu, Lai; Li, Guichen; Guo, Yunbao; Yu, Jinlu (Frontiers in Neurology, 2021)
Background: In rare circumstances, brain arteriovenous malformations (BAVMs) can recruit a transdural blood supply (TBS). The clinical and radiologic characteristics of BAVMs with a TBS are poorly understood. Methods: A retrospective review of the medical records was conducted for adult patients who were admitted for BAVMs from Jan 2013 to Dec 2019. TBSs for BAVMs were divided into 3 types: (1) unilateral TBSs from the external carotid artery (ECA) and/or meningeal branch of the vertebral artery (VA); (2) bilateral TBSs from the ECA and/or meningeal branch of the VA; and (3) meningohypophyseal trunk TBSs of the internal carotid artery. Results: Four hundred and twenty-eight patients were diagnosed with BAVMs during the study period, of whom 30 (7.0%, 30/428) were identified as having a TBS. Type 1, type 2, and type 3 TBSs were identified in 21 (70%, 21/30), 7 (23.3%, 7/30), and 2 (6.7%, 2/30) patients, respectively. Six (20%, 6/30) patients were conservatively managed. Twelve (40%, 12/30) patients underwent endovascular treatment (EVT) of the BAVM through non-TBS feeders. Eight (26.8%, 8/30) patients underwent EVT of the BAVM both through the TBS and non-TBS feeders. The modified Rankin Scale scores at the 3-month follow-up were 0, 1, 2, 4, and 5 in 24 (80%, 24/30), 2 (6.7%, 2/30), 2 (6.7%, 2/30), 1 (3.3%, 1/30), and 1 (3.3%, 1/30) patients, respectively. Good short-term recovery was achieved in 86.7% (26/30) of the patients. The size of the BAVMs with a TBS was larger than that of BAVMs without a TBS. Patients with higher Spetzler-Martin grades tended to have a TBS. No statistical difference was noted between the patients with and without a TBS with regard to age, sex, location, or concurrent aneurysms. Conclusions: This study showed that a TBS was likely to develop in patients with larger BAVMs and that a TBS was likely to be located in the temporal lobe in patients BAVMs with higher SM grades. Weak structures were the primary targets of management. In addition, a BAVM could be embolized via the TBS.